Registry data for use in health technology assessments in Norway - Opportunities and challenges - Gunhild Hagen; Torbjørn Wisløff (Norsk Forening for Epidemiologi, 2021)
Decisions on uptake of medicines and medical devices on health insurance schemes are increasingly based on a health technology assessment (HTA) process. In Norway, the process has included reimbursement of outpatient medicines for two decades. During the past years, in-patient medicines, medical devices and more recently vaccines are all included in the HTA system. In the present article, we outline the Norwegian HTA system including its central components and partners. HTA as a scientific approach puts evidence on efficacy, safety and value of interventions into a broader perspective, explicitly considering relevant factors, among these legal, ethical and organisational aspects of the intervention. Although several combinations of aspects are possible, the most common is an assessment of the relative effectiveness and cost-effectiveness of the intervention. Randomised controlled trials have long been considered the mainstay for assessment of clinical effectiveness pre-launch, while registry data have been used to inform safety post-lunch, by pharmacovigilance. Recently, we have seen a move towards more use of "real world evidence", i.e. data from non-RCT sources, mainly from registries. A model-based approach is often used to assess cost-effectiveness, in this context, different types of evidence from different sources are often synthesized. In this paper we describe the central components of HTA with special emphasis on different observational data sources, such as the unique Norwegian health registries. We finally speculate on future directions for use of observational data in HTA, both in a global and Norwegian setting.